Substance P Receptor in the Rat Heart and Regulation of Its Expression in Long-Term Diabetes - Chottova Dvorakova, Magdalena; Mistrova, Eliska; Paddenberg, Renate; Kummer, Wolfgang; Slavikova, Jana (Frontiers in Physiology, 2018)
Substance P (SP) is involved in the transmission of neural afferents of C fibers in the myocardium. The actions of SP in the heart are extensive and they are mediated by the NK1 receptor, a member of the tachykinin subfamily of G-protein coupled receptors. The receptors have been found in the heart, but to our knowledge, their exact localization in the heart has not been described yet. Here, we investigated presence of NK1 receptor protein in separate rat heart compartments by means of Western blot and its tissue distribution by means of immunofluorescence. Specificity of NK1 receptor-immunolabeling was controlled by preabsorption of the antiserum with its corresponding peptide. Additionally, we investigated expression of gene for NK1 receptor in separated heart chambers by means of RT-qPCR. Relative expression of NK1 receptor mRNA was expressed as a ratio of target gene Cq value to Cq value of control gene – beta-actin. Finally, we studied expression of NK1 receptor in different cell types of heart isolated by laser microdissection. Immunofluorescence showed NK1 receptor immunoreactivity on the surface of some intracardiac neurons and smooth muscle cells of coronary vessels. The results of quantitative RT-PCR indicate expression of mRNA for NK1 receptor in all heart chambers with highest expression in the left atrium. Expression of NK1 receptor was detected in some samples of dissected intracardiac neurons, but not in cardiomyocytes or smooth muscle cells of coronary vessels. In the course of long-term diabetes, a significant down-regulation of the NK1R mRNA was seen in the right atrium and up-regulation in the right ventricle 53 weeks after the induction of diabetes. Our results indicate localization of NK1 receptor in some intracardiac neurons and smooth muscle cells. Increased transcription of the NK1R gene in the diabetic heart may be induced by unidentified genes or factors involved in the development of diabetic cardiomyopathy.